2001
DOI: 10.1210/endo.142.7.8280
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Regulation of Type II Iodothyronine Deiodinase in Human Thyroid Gland*

Abstract: We have studied the expression of type II iodothyronine deiodinase (DII) in human thyroid tumors and cultured human thyroid cells to elucidate the mechanisms involved in the regulation of DII expression in human thyroid gland. Three cases with hyperfunctioning thyroid adenoma, including a case that showed an activating mutation of G(s)alpha with a constitutive activation of cAMP production in cultured cells, and six cases with papillary thyroid carcinoma were analyzed in the present study. Free T(3) was increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
42
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 13 publications
9
42
1
Order By: Relevance
“…A more detailed analysis of the lists of regulated genes (Tables 2-4) confirms previous work on thyroid cells or other cells treated with TSH-or cAMP-enhancing agents for the genes RGS2 (21,22), RGS16 (23), PDE4 (24,25), DIO2 (26)(27)(28), JUNB (19,29), NR4A1 (30), cAMP response element modulator (CREM) (31), TGF␤ (32), IL8 (33), RRAD (34), and EGR1 (19,29).…”
Section: Validation Of Microarray Datasupporting
confidence: 81%
See 1 more Smart Citation
“…A more detailed analysis of the lists of regulated genes (Tables 2-4) confirms previous work on thyroid cells or other cells treated with TSH-or cAMP-enhancing agents for the genes RGS2 (21,22), RGS16 (23), PDE4 (24,25), DIO2 (26)(27)(28), JUNB (19,29), NR4A1 (30), cAMP response element modulator (CREM) (31), TGF␤ (32), IL8 (33), RRAD (34), and EGR1 (19,29).…”
Section: Validation Of Microarray Datasupporting
confidence: 81%
“…Genes regulated in a similar direction in cultured thyrocytes and autonomous adenomas, but that are regulated in the inverse way in papillary carcinomas, might reflect the differentiating action of the TSH-cAMP pathway [DIO2 (26,37), HGD (38), FHL1 (39), ITPR1 (39,40), CRABP1 (40,41), and ADM (40)], whereas common expression in the TSH-stimulated thyrocytes, autonomous adenomas, and papillary carcinomas concerns possibly proteins involved in the control or support of cell growth [EFHD2, IER2, KLF6 (10), EGR1 (10), GADD45B, and JUN]. One puzzling common property of autonomous adenomas and papillary carcinomas is the down-regulation of a number of immediate early genes [NR4A1, JUNB (10), KLF10, and ZFP36].…”
Section: Discussionmentioning
confidence: 99%
“…For T 3 , the efficiency of conversion was increased Ϸ2-fold upon TSH or forskolin treatment. The preference in T 3 over T 4 release upon stimulation can easily be explained by the action of type II iodothyronine deiodinase and its well known activation by TSH in the human thyroid (27). Altogether, in vitro stimulation of the TSH͞cAMP cascade reconstituted the key findings of AAs: increased expression of rate-limiting endocytic catalysts leading to accelerated Tg endocytosis and conversion into thyroid hormones.…”
mentioning
confidence: 80%
“…In contrast, type 3 iodothyronine deiodinase (DIO3, D3) catalyzes the inactivation of T 4 and T 3 via inner ring deiodination . Several studies have shown an association between thyroidal status and tumor pathogenesis (Pinto et al 2011, Kim & Cheng 2013 while several reports have documented changes in the expression of deiodinases in benign and malignant tumors (Huang et al 2001, Murakami et al 2001, de Souza Meyer et al 2005, Dentice et al 2007, Meyer et al 2007.…”
Section: Introductionmentioning
confidence: 99%